Hydrodynamic Numerical Simulation of the Sipaikou Reach of the Yellow River in Ningxia Based on MIKE 3 - LIU Xin; LI Chunguang; LAN Bin; HUANG Chuanji; HE Jinsha (Renmin Zhujiang)
In order to study the flow of the 4.530 km reach under the influence of the spur dikesafter the Sipaikoureach of the Yellow River in Ningxia runs under the “curve cut-off” project,and provide decision-making references and suggestions for the safe and stable operation of theproject,aiming at the unique terrain and geomorphological features of the reach, this paperconstructs a three-dimensional hydrodynamic mathematical model of Sipaikou with the help of MIKE 3software, and verifies the applicability and correctness of the built model with the hydrologicaldata measured on site in July 18. The calculation results show that, the elliptical vortex runningcounterclockwise with a long radius of about 128.824 m and a short radius of about 71.939 m wasformed at the contact position of the end of the spur dikes and river intake.After implementationof the “curve cut-off” project,there is a sudden change in the boundary conditions of theriverbed, resulting in very complicated flow motion in the study area. If not controlled, it willcause severe river bed erosion and deformation.